Implikasi Pengawasan Persaingan Usaha Terhadap Perkembangan Ekonomi Digital (Lex Jurnalica, 2023)
This paper will explain the digital economy's development to impact business actors who will carry out digital transformation and innovation. The position of business actors, both individuals, and legal entities and unincorporated, makes the process of supervision and enforcement of business competition laws against the development of the digital economy must be carried out actively. The potential for unfair business competition will often occur, especially in the digital world, as the level of proof to the digital world has not yet gained a place against the enactment of rules governing the digital economy. This type of research is normative research with a conceptual approach, legislation, and comparison. In this paper, it can be concluded that the digital economy's development is changing the economic situation, which is conventional to electronically or, in other words, all transactions are in the internet network.Â  The existence of harmonization between institutions and regulatory efficiency, as well as the role of the Business Competition Supervisory Commission to maintain a healthy business competition climate in the digital economy, is not only limited to providing supervision and law enforcement but there are essential things that must be done is to create fair business competition and based on community welfare. Â Keywords: Digital Economy, Supervision, Business Actors